Arts-based research: poetic creations unfolding worlds (Palíndromo, 2019)
This article aims to contribute to the studies on Arts-Based Research (ABR), bringing a brief history of this methodology and emphasizing the power of the poetic gesture to provide broad ways of research. The article revisits the work of Elliot Eisner, of the A/r/tography group and highlights the contribution of the challenges posed by Jan Jagodzinski and Jason Wallin, proposing deviant creations. By destabilizing the gaze of the common sense and opening space for invention and encounter, the ABR can operate, rather than an epistemological construction, an ontological action – a become-art, an aesthetic of existence, a belief in the possibility of the world. The essay also proposes visits to the Nietzchean gestures, which locate art at the center of life and through the deviant thinking of Deleuze, which spreads out in multiplicities to produce beginnings.
Keywords: research; education; art; experience-of-the-outside